The influence of small-sided games training on passing and endurance ability in men's futsal team - Indrayogi Indrayogi; Davi Sofyan; Rudi Rudi; Riza Sukma Fauzi (Universitas Sriwijaya, 2023)
Passing is one of the basic techniques of futsal that players really need. While Endurance is a state or physical condition of the body that can work for quite a long time. This study aims to determine the effect of the small side games training method on the passing and endurance abilities of Banteng Muda Indonesia Majalengka male futsal athletes. The research method used was a quasi-experimental with a pretest-posttest control group design, the population in this study were Banteng Muda Indonesia male futsal athletes. The sampling used is probability sampling with the condition that all objects are all Banteng Muda Indonesia male futsal athletes. The number of samples in this study were 20 players. The instruments used in this study were passing tests and endurance tests. Data analysis used the T test. The results of the T-test for passing abilities obtained tcount = -3,644 with sig 0.002 <0.05 so HO was accepted, and for endurance T-test results obtained tcount = -5710 with sig 0.000 <0.05 so HO accepted. The conclusion is that there is an influence on the ability of passing and endurance between the Experiment group and the Control group after being given different exercises for 12 meetings. Then the researcher provides recommendations especially for coaches and generally for all futsal players by providing a form of training that can improve passing ability and endurance such as variations of small side game exercises.